Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Number: 2
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Representing Black Britain: Black and Asian Images on Television - Malik, Sarita (SAGE Publications, Limited, 2001)
'One of the most important books on race, representation and politics to come along in a decade' - Henry Giroux, Penn State University Representing Black Britain offers a critical history of Black and Asian representation on British television from the earliest days of broadcasting to the present day.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Interview with Deyfou-lah Sani Bah-Traore on the Togolese Game Origin - the Rise of Dzitri - Kienzl, Lisa; Bah-Traore, Deyfou-lah Sani (Gamevironments, 2019)
In the Togelese game Origin - the Rise of Dzitri that was developed in Lome, the character Edoh takes you on a journey to historic places in the city to revive the spirit of Dzitri. Deyfou-lah Sani Bah-Traore, programmer and game developer, spoke with Lisa Kienzl about his and his Teammate s work on Origin - the Rise of Dzitri
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Interview With Ryan Sumo, Lead Artist/Business Developer At Squeaky Wheel Studio - Radde-Antweiler, Kerstin; Sumo, Ryan (Gamevironments, 2018)
Interview with Ryan Sumo, Lead Artist/Business Developer at Squeaky Wheel Studio
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With Ben Joseph P. Banta, Founder Of Ranida Games - Radde-Antweiler, Kerstin; Banta, Ben Joseph P. (Gamevironments, 2018)
Interview With Ben Joseph P. Banta, Founder Of Ranida Games
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With The Creator Of Boo! Dead Ka! Game - Radde-Antweiler, Kerstin; Prieto, Kurt (Gamevironments, 2018)
Interview with With Kurt Prieto, Games Designer Of Boo! Dead Ka! Game
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio - Zeiler, Xenia; Zainuddeen, Fahadh (Gamevironments, 2018)
Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio, Hyderabad, India
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio - Zeiler, Xenia; Kumar, Avinash (Gamevironments, 2018)
Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games - Zeiler, Xenia; Singh, Avichal (Gamevironments, 2018)
Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games, Pune, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Satyajit Chakraborty, Founder of Flying Robot Studios, Kolkata, India - Zeiler, Xenia; Chakraborty, Satyajit (Gamevironments, 2018)
Accepted: 2020-03-25T23:30:08Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé